Internalisasi nilai-nilai karakter dalam kegiatan belajar santri tpq hidmatul hasan sukodadi - Romadhoni, Muhammad Fadil (Maliki Interdisciplinary Journal, 2025)
This study aims to identify the process of character value internalization in the learning activities of students at TPQ Hidmatul Hasan Sukodadi, Paiton, Probolinggo. Employing a qualitative approach with participatory observation methods, the researcher engaged directly in teaching activities to capture the natural dynamics of value formation. The findings indicate that character values such as discipline, responsibility, honesty, and empathy are instilled through habituation, modeling, and close social interaction between teachers and students. Value internalization occurs not only through explicit instruction but also through a religious that supports moral development. As a non-formal educational institution, TPQ plays a strategic role in shaping children’s. Recommendations include strengthening teacher capacity, involving parents, and fostering synergy across learning environments to sustain character values beyond the classroom.